Ресторани і трактири в Шевченковій повісті «Художник» (з нових коментарів) - Боронь, О. (Слово і Час, 2022)
Вивчення згаданих у повісті ресторанів і трактирів додає чимало нових деталей до Шевченкової біографії. На підставі свідчень сучасників, описів із тогочасних художніх творів, інформації з путівників та міських довідників наведено характеристики петербурзьких ресторанів і кондитерських Александра, Деллі, Дюме, Клеє, Сен-Жоржа, римських кафе Лепрі та Греко. Д оведено, що кухмістерська мадам Кароліни Юргенс розташовувалася не на 6-й лінії Васильєвського острова, а на 3-й, поблизу Великого проспекту, неподалік винного погребу Я. Фохтса на 2-й лінії. Обґрунтовано припущення, що згаданий у повісті трактир «Берлин» на розі 6-ї лінії і Академічного провулка містився за сучасною адресою 6-та лінія, 3 / Академічний провулок, 10, оскільки в цьому будинку, на відміну від наріжного навпроти, від початку ХІХ ст. працював винний магазин. Besides specifying or clarifying the current address of the restaurants and taverns mentioned in the story, it appeared necessary to give a minimum description of this or that eating-house as most of the relevant names and cases of comparing and contrasting some of them say little to a common reader and sometimes to a specialist as well. The study of these restaurants and taverns adds many new details to Shevchenko’s biography. Based on the information of the author’s contemporaries (mostly from the 1830s—1840s), descriptions in the fiction of the time, as well as city guides and directories, the paper presents characteristics of St. Petersburg restaurants and confectioneries of Alexander, Delli, Dume, Klee, Saint Georges, the Roman cafes Lepri and Greco. The paper proves that Madame Jurgens’ eating-house was located not on the sixth line of Vasilyevsky Island, but the third one, near the Great Avenue, not far from the wine cellar of Ja. Vochts on the second line. It refutes the erroneous localization by M. Morenets who believed that Jurgens canteen worked in a house at the modern address 6 Buzky Lane / 7 the 6th line. In fact, there was a tavern “The Golden Anchor”, which is also visited by the characters of the story. There is evidence that allows assuming that the tavern “Berlin” mentioned in the story as one in the corner of the 6th line and Academic Lane was located at the modern address 3 6th line / 10 Academic Lane, because since the early 19th century there was a wine shop in this particular building, and not in the one at the opposite corner. When not lacking money to pay, Shevchenko and his Academy classmates had lunch mostly in Madame Jurgens’ eating-house. If they could afford it, getting paid for a portrait or something, they visited the restaurant Klee. K. Bryullov could sometimes invite them for dinner at Delli’s confectionery or Alexander’s restaurant. Shevchenko also knew some other aristocratic eating-houses and, of course, just heard of Roman cafes from others.